2013
DOI: 10.1177/039463201302600108
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Corilagin on Post-Parasiticide Liver Fibrosis in Schistosomiasis Animal Model

Abstract: The first two authors contributed equally to this study This study investigates the effects and possible molecular mechanisms of corilagin extraction on prevention of Schistosoma japonicum ova-induced granulomas and liver fibrosis. As a result, under a light microscope, when compared to a model group, the corilagin group showed smaller granulomas, less liver cell denaturation and less inOammatory cell infiltration, and the connective tissues were significantly decreased. By Masson staining, the liver sections … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…Furthermore, it was confirmed that corilagin is an inhibitor of TNF-α [16] and can restrain radiation-induced microglia activation via suppression of the NF-κB pathway [17], and corilagin is protective against GalN/LPS-induced liver injury through suppression of oxidative stress and apoptosis [18]. Our recent research showed that corilagin can alleviate the hepatic fibrosis caused by egg granuloma in Schistosoma japonicum infection [19]. …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it was confirmed that corilagin is an inhibitor of TNF-α [16] and can restrain radiation-induced microglia activation via suppression of the NF-κB pathway [17], and corilagin is protective against GalN/LPS-induced liver injury through suppression of oxidative stress and apoptosis [18]. Our recent research showed that corilagin can alleviate the hepatic fibrosis caused by egg granuloma in Schistosoma japonicum infection [19]. …”
Section: Introductionmentioning
confidence: 99%
“…Some of our previous studies on Corilagin have confirmed its effects on ameliorating sepsis (21) as well as its anti-oxidative and anti-inflammatory effects (29) and suppressive effects on HSV-1 encephalitis (30). Moreover, our studies have demonstrated that IL-13 is associated with the multi-target effects of Corilagin on relieving schistosome egg-induced liver fibrosis (12, 32, 33). On the basis of the above findings, further study of Corilagin is warranted.…”
Section: Introductionmentioning
confidence: 75%
“…Fibrosis was scored as 5 grades according to the METAVIR scoring system (51, 52): F0, no fibrosis; F1, portal fibrosis without septa; F2, portal fibrosis with few septa; F3, numerous septa without cirrhosis; and F4, cirrhosis. The degree of hepatic fibrosis was detected to elevate the score F0(2 0 )=1, F1(2 1 )=2, F2(2 2 )=4, and F3(2 3 )=8 (12). The mRNA levels of Alpha α-SMA further demonstrated that the degree of hepatic fibrosis from the Corilagin group was significantly alleviated (P<0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Following our previous protocols (Huang et al, ; Zhou et al, ), total RNA from liver tissues and cells was isolated using RNAiso Plus following the manufacturer's instructions. cDNAs were produced using a PrimeScript RT reagent kit and incubated at 37°C for 15 min and 85°C for 5 s. Real‐time PCR reactions were performed using a StepOne Plus device (Applied Biosystems) at 95°C for 10 s followed by 40 cycles of 95°C for 5 s and 60°C for 20 s according to the instructions provided by the SYBR Premix Ex Taq kit.…”
Section: Methodsmentioning
confidence: 99%